2008
DOI: 10.1161/circulationaha.108.768283
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Inhibition of Thromboxane Biosynthesis by Acetylsalicylic Acid

Abstract: Background-Incomplete inhibition of platelet thromboxane generation, as measured by elevated urinary 11-dehydro thromboxane B 2 concentrations, has been associated with an increased risk of cardiovascular events. We aimed to determine the external validity of this association in aspirin-treated patients enrolled in the Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management and Avoidance (CHARISMA) trial and to determine whether there are any modifiable factors or interventions that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
94
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(107 citation statements)
references
References 38 publications
12
94
0
1
Order By: Relevance
“…We also observed higher levels of 5‐LOX products (namely, the eicosapentaenoic acid–derived 5S‐HEPE, the LA‐derived 9‐HODE, the AA‐derived 5‐HETE, and the α‐linolenic acid–derived 9‐HOTrE) in women. This is in accordance with previous findings that androgens downregulate 5‐LOX product formation 9, 10, 37, 38. Most of these constitutive differences in oxylipid levels persisted after aspirin treatment and no sex‐specific effect of aspirin on oxylipid was observed, consistent with our previous findings in this population 4, 9, 11, 12, 39…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also observed higher levels of 5‐LOX products (namely, the eicosapentaenoic acid–derived 5S‐HEPE, the LA‐derived 9‐HODE, the AA‐derived 5‐HETE, and the α‐linolenic acid–derived 9‐HOTrE) in women. This is in accordance with previous findings that androgens downregulate 5‐LOX product formation 9, 10, 37, 38. Most of these constitutive differences in oxylipid levels persisted after aspirin treatment and no sex‐specific effect of aspirin on oxylipid was observed, consistent with our previous findings in this population 4, 9, 11, 12, 39…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms underlying variability in aspirin response are poorly understood. Incomplete COX‐1 inhibition has been observed in several settings;9, 10 however, poor response despite complete COX‐1 inhibition has also been reported 9, 11…”
Section: Introductionmentioning
confidence: 99%
“…The first observation is in line with the previous studies by Eikelboom et al in which 11‐dehydro‐TXB 2 was found to be a good predictor of MACEs in a high cardiovascular risk population treated with aspirin 9, 10. The risk of MACE occurrence in these studies, when 2 extreme quartiles of 11‐dehydro‐TXB 2 were compared, was between 1.66 and 1.8 times higher in the upper quartile.…”
Section: Discussionsupporting
confidence: 91%
“…Actually, in the multivariate model only 3 other variables contributed to 11‐dehydro‐TXB 2 predictive properties: LVEF on admission, presence of diabetes mellitus, and multivessel disease. This model proved to have a good prediction capability with an area under the curve of 0.806 and OR for 11‐dehydro‐TXB 2 of 1.581 (95% CI 1.095–2.329), results similar to those presented by Eikelboom et al 9, 10…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation